The Impact of Team Empowerment on Virtual Team Performance: The Moderating Role of Face-to-Face Interaction - Kirkman, Bradley L.; Rosen, Benson; Tesluk, Paul E.; Gibson, Cristina B. (Academy of Management Journal, 2004)
We investigated the relationship between team empowerment and virtual team performance and the moderating role of the extent of face-to-face interaction using 35 sales and service virtual teams in a high-technology organization. Team empowerment was positively related to two independent assessments of virtual team performance? process improvement and customer satisfaction. Further, the number of face-to-face meetings moderated the relationship between team empowerment and process improvement: team empowerment was a stronger predictor for teams that met face-to-face less, rather than more, frequently.